Headaches in pregnancy. (23rd May 2014) - Revell, Kirsty; Morrish, Paul
<x xml:space="preserve">Abstract</x> Key content Headaches in pregnancy and the postnatal period are common and usually benign but can herald intracranial catastrophe. Assessment of headache in pregnancy is an essential skill for obstetricians and general practitioners. Pregnancy can alter migraine aura and may trigger attacks of aura without a headache. Headache may be the only symptom of cerebral venous thrombosis. If cerebral venous thrombosis is suspected, expert opinion should be sought and urgent brain imaging considered. Neurological conditions were the third most common cause of death and ahead of sepsis in the Confidential Enquiries into Maternal Deaths in the United Kingdom 2006–2008 report (when considering direct and indirect causes). Learning objectives To revise the 'red flag' features and the differential diagnosis of headache in pregnancy. To recognise when referral to a neurologist and urgent brain imaging is indicated. To review the management of common causes of headache in pregnancy. Ethical issues Should obstetricians ever manage a neurological problem in pregnancy without neurological advice?